Analysis of Religious Moderation Values in Extracurricular Activities - Eka Diana; Umi Farokhah (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2023)
This research aims to analyze the values of religious moderation in extracurricular activities at Tunas Luhur High School. This research uses a qualitative approach with a case study type. Data collection techniques in this study used in-depth interviews, participant observation and documentation. The informants in the study were the principal, vice principal of curriculum and students. The data obtained were analyzed using several stages, namely data reduction, data presentation and conclusion drawing. The results showed that extracurricular activities carried out at Tunas Luhur High School consisted of extracurricular activities which were part of Islamic religious education and extracurricular activities that were mandatory and specialization. Analysis of the values contained in extracurricular activities consists of the values of usefulness, tolerance, and justice so that with extracurricular activities carried out students can apply the values of religious moderation in the life of the society and nation.